An 8-bit successive-approximation register analog-to-digital converter operating at 125 kS/s with enhanced comparator in 180 nm CMOS technology - Zghoul, Fadi Nessir; Al-Bakrawi, Yousra Hussein; Etier, Issa; Kannan, Nithiyananthan (International Journal of Electrical and Computer Engineering (IJECE), 2024)
Data converters are necessary for the conversion process of analog and digital signals. Successive approximation register (SAR) analog-to-digital converters (ADC) can achieve high levels of accuracy while consuming relatively low amounts of power and operating at relatively high speeds. This paper describes a design of 8-bit 125 kS/s SAR ADC with a proposed high-speed comparator design based on dynamic latch architecture. The proposed design of the comparator enhances the performance compared to a conventional dynamic comparator by adding two parallel clocked input complementary metal-oxide semiconductor (CMOS) transistors which reduce the parasitic resistance in the latch ground path and serve to minimize the latch delay time. The design of each sub-system for the ADC is explained thoroughly, which contains a sample and hold circuit, successive approximation register, charge redistribution types digital-to-analog converter, and the new proposed comparator. The proposed design is implemented using 180 nm CMOS technology with a power supply of 1.2 V. The average inaccuracy in differential non-linearity (DNL) is +0.6/−0.8 LSB (least significant bit), and integral non-linearity (INL) is +0.4/−0.7 LSB. The proposed design exhibits a delay time of 157 ps at 1 MHz clock frequency.